Quality of the tourist service in the Magic Town of El Fuerte, Sinaloa: descriptive analysis - Olmos-Martínez, Elizabeth (2024)
The quality of tourism services is a crucial element for the development and growth of companies; globalisation implies the need for information for decision-making in a competitive world. This research aimed to analyse the dimensions and criteria of the quality of service offered by tourism providers in the Magical Town of El Fuerte, Sinaloa. The methodology is quantitative, descriptive and cross-sectional. It is based on an analysis of the perception of the service provided using five dimensions with different criteria established in the SERVQUAL model and analysed under the SERVPERF model. A total of 383 surveys were applied to tourists and visitors who consumed services in the different establishments; the instrument consists of 24 items: 22 of them to evaluate the quality of service and two to know the price-service relationship and quality of service in general on a Likert scale; the application period was during April and May 2023. The results indicate that empathy, assurance, and responsiveness were the best evaluated of the five dimensions analysed for service quality. The majority of respondents perceive the quality of service as excellent, which indicates that the tourist destination provides acceptable conditions for the experience. However, the results are a tool for decisionmaking aimed at continuous improvement in the criteria evaluated.